2004
DOI: 10.2337/diacare.27.10.2560-a
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors of Sudden Sensorineural Hearing Loss in Diabetic Patients

Abstract: Associations between the characteristics of general practitioners and their patients with type 2 diabetes O besity is an important cardiovascular risk factor in type 2 diabetes (1). Physician characteristics such as age and sex are related to counseling for overweight (2). Other physician characteristics may also be related. Patients indicated greater confidence in nonobese versus obese physicians. Whether this translates into increased success in obesity management is unknown (3). We aimed to study associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 1 publication
0
31
0
Order By: Relevance
“…Significant effects of steroids on hearing recovery have been reported 14,15 . We also documented the benefits of high‐dose glucocorticoid therapy and suggested its use for SSNHL in diabetic patients 13 . Usually, high‐dose steroids are not used in diabetic patients because of possible side effects such as worsening hyperglycemia.…”
Section: Discussionmentioning
confidence: 88%
“…Significant effects of steroids on hearing recovery have been reported 14,15 . We also documented the benefits of high‐dose glucocorticoid therapy and suggested its use for SSNHL in diabetic patients 13 . Usually, high‐dose steroids are not used in diabetic patients because of possible side effects such as worsening hyperglycemia.…”
Section: Discussionmentioning
confidence: 88%
“…Several studies have reported a consistent association between microangiopathy and SSHL (3,12,31,32). Aimoni et al (19) stated that the risk of developing SSHL tended to increase with increasing number of cardiovascular risk factors.…”
Section: Microangiopathy As One Of the Mechanismsmentioning
confidence: 96%
“…It has been believed that bacteria- or virus-induced chronic inflammation could cause microvascular injury, vascular endothelial dysfunction, and atherosclerosis, leading to an increased risk of cochlear ischemia [7, 12, 13]. Furthermore, susceptibility to genetic thrombosis or cardiovascular risk factors would further aggravate the risk of cochlear ischemia [14, 15]. The NLR in peripheral blood has not only been proved to be one of the definitive markers of chronic inflammation in the cardiovascular system, it is also a reliable predictor of functional recovery after vascular disease.…”
Section: Discussionmentioning
confidence: 99%